2007
DOI: 10.1007/s00535-007-2032-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leptin on stress-induced changes of caspases in rat gastric mucosa

Abstract: Cold-restraint stress decreases the antioxidant capacity of stomach tissue while activating oxidants, and induces apoptosis by an increase in caspase immunoreactivity. The presence of leptin reverses these mechanisms and suppresses the apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Another study demonstrated that sodium bisulfite and sodium sulfite at various doses (125, 250 or 500 mg/kg body weight) significantly increase DNA damage on stomach and different organs (Meng et al, 2004). Our previous study also showed that cold-restraint stress caused apoptosis in gastric mucosa secondary to a decrease in antioxidant capacity and an increase in oxidant activity (Ercan et al, 2007). Recent studies showed that indomethacin and helicobacter pylori induce mitochondrial pathology that ultimately activates the mitochondrial pathway of apoptosis in gastric mucosa to develop gastropathy (CalvinoFernandez et al, 2008;Maity et al, 2009).…”
Section: Discussionmentioning
confidence: 87%
“…Another study demonstrated that sodium bisulfite and sodium sulfite at various doses (125, 250 or 500 mg/kg body weight) significantly increase DNA damage on stomach and different organs (Meng et al, 2004). Our previous study also showed that cold-restraint stress caused apoptosis in gastric mucosa secondary to a decrease in antioxidant capacity and an increase in oxidant activity (Ercan et al, 2007). Recent studies showed that indomethacin and helicobacter pylori induce mitochondrial pathology that ultimately activates the mitochondrial pathway of apoptosis in gastric mucosa to develop gastropathy (CalvinoFernandez et al, 2008;Maity et al, 2009).…”
Section: Discussionmentioning
confidence: 87%
“…Stressors of different types [25][26][27][28] or treatments with glucocorticoids [29][30][31][32] induce apoptosis in different tissues, including testicular germ cells [33]. Fluid from follicles of women whose oocytes were not fertilized contained cortisol levels significantly higher than in the fluid from follicles containing successfully fertilized oocytes [34].…”
Section: Introductionmentioning
confidence: 99%
“…The ischemic condition caused an increase in the level of H 2 O 2 , which, in conjugation with O 2 generates OH. Lipid peroxidation induced by oxygen-free radicals seems to play a critical role in the pathogenesis of acute gastric mucosal injury in both experimental animals and humans [32]. Oxidative stress and caspases have been implicated as potential mediators of cell death [30].…”
Section: Discussionmentioning
confidence: 99%